2016
DOI: 10.21037/jtd.2016.10.20
|View full text |Cite
|
Sign up to set email alerts
|

Three-field lymph node dissection in treating the esophageal cancer

Abstract: There are many controversies in lymphadenectomy for thoracic esophageal cancer, and whether 3-field lymphadenectomy or 2-field lymphadenectomy is better have still been in doubt. The aim of this article is to review the role of the lymph node dissection by introducing the merits and demerits in 3-field lymphadenectomy, and the development in lymphadenectomy's selection, treatment and diagnosis. All the literatures related to esophageal lymphadenectomy and minimally invasive surgery (MIE) were searched in PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 73 publications
0
22
0
1
Order By: Relevance
“…However, in clinical practice, although extended systematic nodal dissection is regarded as the best treatment for patients, the possibility of omitting positive lymph nodes also exists and a high occurrence of postoperative complications makes it difficult for surgeons to choose the best strategy of lymph node dissection [ 21 , 22 ]. Surgeons face a dilemma about how to perform lymph node dissection and they must make this decision based on their experience [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical practice, although extended systematic nodal dissection is regarded as the best treatment for patients, the possibility of omitting positive lymph nodes also exists and a high occurrence of postoperative complications makes it difficult for surgeons to choose the best strategy of lymph node dissection [ 21 , 22 ]. Surgeons face a dilemma about how to perform lymph node dissection and they must make this decision based on their experience [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several systematic reviews and meta-analyses have been reported (42)(43)(44). Shang et al analyzed the longterm survival and showed that 3FD was superior to 2FD for patients with LN metastasis in the cervical or upper mediastinal LNs (44). Ma et al reported a meta-analysis and demonstrated that 3FD could lead to improved survival rates following an esophagectomy (43).…”
Section: Safety and Efficacy Of 3fd And Comparison With 2fdmentioning
confidence: 99%
“…Esophagectomy with two-field lymphadenectomy or three-field lymphadenectomy (3FL) is the typical strategy for resectable EC. However, the extent of lymph node dissection is still controversial 11. Radiotherapy or chemoradiotherapy is a prior choice for unresectable EC.…”
Section: Introductionmentioning
confidence: 99%
“…Involved-field irradiation and elective nodal irradiation are both available. No matter which method is used, it is a fact that EC has a poor survival and the lymph node recurrence is a main failure 1114. Though much experience in patterns of LNM for EC has been accumulated in past decades, it is challenging to evaluate the status of LNM and to make a reasonable treatment plan for different patients.…”
Section: Introductionmentioning
confidence: 99%